2018
DOI: 10.1055/s-0038-1676485
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Practices and Perceived Optimal Breastfeeding Interventions among Low-Income Women Delivering at a Baby-Friendly Hospital

Abstract: Objective To determine infant feeding practices of low-income women at a Baby-Friendly Hospital and to ascertain breastfeeding interventions they believe would increase exclusive breastfeeding. Study Design This cross-sectional study occurred at a tertiary care Baby-Friendly Hospital. Low-income women without breastfeeding contraindications were recruited at scheduled obstetrician/gynecologist appointments within 6 to 9 months of delivering a term, nonanomalous infant. Participants completed a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…As reported previously, 6 while in the hospital, women who nonexclusively breastfed at postpartum day 2 were less likely to ask for in-person breastfeeding help-and more likely to report inperson help did not solve their breastfeeding issue-when compared with women who exclusively breastfed or exclusively formula fed at postpartum day 2. 6 In addition, women were asked to select from a list of in-person or virtual breastfeeding support options that they believed would have helped them prolong their duration of exclusive breastfeeding. All women reported having on-demand access to videos on breastfeeding and normal infant behavior would have helped them exclusively breastfeed.…”
supporting
confidence: 66%
See 4 more Smart Citations
“…As reported previously, 6 while in the hospital, women who nonexclusively breastfed at postpartum day 2 were less likely to ask for in-person breastfeeding help-and more likely to report inperson help did not solve their breastfeeding issue-when compared with women who exclusively breastfed or exclusively formula fed at postpartum day 2. 6 In addition, women were asked to select from a list of in-person or virtual breastfeeding support options that they believed would have helped them prolong their duration of exclusive breastfeeding. All women reported having on-demand access to videos on breastfeeding and normal infant behavior would have helped them exclusively breastfeed.…”
supporting
confidence: 66%
“…3,17 Various explanations have been proposed for this racial inequity, such as a lack of support from professionals and family members, lack of knowledge of breastfeeding benefits, and lack of education on how to overcome common breastfeeding issues. 3,6,17,18 The BFF app was developed using findings from our previous study that identified specific barriers that low-income women believed prevented them from exclusively breastfeeding 6 and was further optimized by multiple focus groups of target end users (low-income, predominantly black women). However, the complex postpartum environmental factors of our study population may have limited the BFF app's effectiveness to increase breastfeeding equity in this high-needs population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations